The fear factor—Snakes in Africa might be at an alarming extinction risk - Harith Farooq; Jonas Geldmann (Conservation Letters, 2024)
Abstract Snakes in Africa are responsible for over 20,000 deaths annually, their indiscriminate killing. As a result, snakes are vulnerable to human population increases even at low intensities. Thus, the predicted doubling of Africa's population by 2050 is likely to pose a disproportionate threat to snakes compared to other taxa. Here we quantify the current and future overlap of snake distributions and human population density under three scenarios of population growth. We find that by 2050, on average, 71% of snake ranges of conservation concern will overlap with areas occupied by ten or more people per km2, a 22% increase from 2020. In addition, the number of Least Concern species with most of their range within areas with high human population density will more than double, likely increasing the number of threatened species over the next decades. Our results call for immediate policy action targeting people's perceptions and fears of snakes, and incorporating snakes directly into development and conservation plans to reduce the impact of future urban expansions across Africa.